Structural optimization of a CT guided robotic arm based on static analysis. (2018) - Ghosh, Taniya; Roy, Ayan; Mishra, Ruby; Shubham Kamlesh, Shah
Abstract: A robotic arm can be used in fields like surgery, radiology, detection of cancer, tumour detection surgeries such as biopsy with paramount precision at low cost and less postoperative pain for the patients. A robotic arm is designed that can reach the target point by just taking the coordinate points as input. In this research paper the main focus is on finding out the deformation that would occur over a period of time due to its self-weight during its idle position and cause error while functioning. Designing and simulation of the robotic arm is done in SOLIDWORKS 2016. Structural analysis of the robotic arm based on Von mises stress and strain have been analysed in order to find the failure points which can occur after long time use of this robotic arm which are highlighted in this paper using ANSYS R15. The design is modified to reduce the stress in the link which can cause failure. The modified design was analysed again and there was a significant reduction in the deformation of the needle end by 59%.